2014
DOI: 10.4103/0972-124x.142437
|View full text |Cite
|
Sign up to set email alerts
|

Cementoenamel junction: An insight

Abstract: The location and nature of cemento-enamel junction (CEJ) are more than descriptive terms used simply to describe some aspects of tooth morphology; however, CEJ gains a lot of clinical significance due to various measurements dependent on it. It may be necessary to determine the location and pathological changes occurring at CEJ to make a diagnosis and treat diseases pertaining to epithelial attachment and gingival margin. However, the information related to CEJ is not discussed commonly. Hence, the present rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
2
26
0
1
Order By: Relevance
“…(12,24,25) These differences can be attributed to the difference in the age profile of the participants. (26) The present study showed that the prevalence of DH in the mandibular premolars and canines is higher. Similar studies also have reported a higher prevalence of DH in premolars.…”
Section: Discussionsupporting
confidence: 49%
“…(12,24,25) These differences can be attributed to the difference in the age profile of the participants. (26) The present study showed that the prevalence of DH in the mandibular premolars and canines is higher. Similar studies also have reported a higher prevalence of DH in premolars.…”
Section: Discussionsupporting
confidence: 49%
“…All patients received thorough oral prophylaxis and oral hygiene guidelines 1 week before the clinical examination to prevent any signs of gingival inflammation. Location of Cemento‐enamel junction (CEJ) was done using a combination of conventional method (feeling the catch at the cervical region when the probe is moved from a smoother enamel to a rougher root surface) and radiographic method (demarcation between more radio‐dense enamel and less radio‐dense root cementum) . A point of 3 mm apical to previously located CEJ was marked on tooth #4, #5, #12, and #13, respectively, and this point is used as a reference for the measurement of attached gingival thickness and corresponding buccal bone thickness.…”
Section: Methodsmentioning
confidence: 99%
“…ing the catch at the cervical region when the probe is moved from a smoother enamel to a rougher root surface) and radiographic method (demarcation between more radio-dense enamel and less radio-dense root cementum). 18 A point of 3 mm apical to previously located CEJ was marked on tooth #4, #5, #12, and #13, respectively, and this point is used as a reference for the measure-…”
Section: Methodsmentioning
confidence: 99%
“…The importance of CEJ in periodontics and restorative odontology is increasing with aging of an individual (11,12). The neck region of the tooth was mostly investigated for cervical and radicular caries, increased sensitivity of the teeth and the frequent occurrence of cervical erosion (13,14).…”
Section: Discussionmentioning
confidence: 99%